(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In this work are analyzed the carabidocoenosis found by means of pitfall traps in vineyards of the province of Brescia (Lombardy) different in the type of agronomical conduction. The results showed that in the milled field the summer peak of occurrences is markedly anticipated, while the vineyards treated with pesticides showed a strong impoverishment of the Carabid fauna both in number of species and of specimens if compared with the untreated ones.